2018
DOI: 10.3389/fpls.2018.01721
|View full text |Cite
|
Sign up to set email alerts
|

Role for Arabidopsis PLC7 in Stomatal Movement, Seed Mucilage Attachment, and Leaf Serration

Abstract: Phospholipase C (PLC) has been suggested to play important roles in plant stress and development. To increase our understanding of PLC signaling in plants, we have started to analyze knock-out (KO), knock-down (KD) and overexpression mutants of Arabidopsis thaliana, which contains nine PLCs. Earlier, we characterized PLC2, PLC3 and PLC5. Here, the role of PLC7 is functionally addressed. Promoter-GUS analyses revealed that PLC7 is specifically expressed in the phloem of roots, leaves and flowers, and is also pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 120 publications
(208 reference statements)
0
11
0
Order By: Relevance
“…Recent reviews sequentially reported 54 genes (Francoz et al, 2015) and 82 genes (Phan & Burton, 2018). Since then, 12 additional genes have been characterized (Fabrissin et al, 2019;Kunieda, Hara-Nishimura, Demura, & Haughn, 2019;Li et al, 2018;Shimada et al, 2018;Šola, Gilchrist, et al, 2019;Takenaka et al, 2018;van Wijk et al, 2018;Voiniciuc et al, 2018;Wang et al, 2019;Yang et al, 2019) bringing the list to 94 genes so far. They constitute the continuously growing MSC toolbox that participate to a proper seed mucilage production and release in A. thaliana (Francoz et al, 2015;Voiniciuc, Yang, Schmidt, Günl, & Usadel, 2015).…”
Section: Diversity Of Myxodiasporymentioning
confidence: 99%
“…Recent reviews sequentially reported 54 genes (Francoz et al, 2015) and 82 genes (Phan & Burton, 2018). Since then, 12 additional genes have been characterized (Fabrissin et al, 2019;Kunieda, Hara-Nishimura, Demura, & Haughn, 2019;Li et al, 2018;Shimada et al, 2018;Šola, Gilchrist, et al, 2019;Takenaka et al, 2018;van Wijk et al, 2018;Voiniciuc et al, 2018;Wang et al, 2019;Yang et al, 2019) bringing the list to 94 genes so far. They constitute the continuously growing MSC toolbox that participate to a proper seed mucilage production and release in A. thaliana (Francoz et al, 2015;Voiniciuc, Yang, Schmidt, Günl, & Usadel, 2015).…”
Section: Diversity Of Myxodiasporymentioning
confidence: 99%
“…The phenomenon of seed senescence being associated with mitochondrial damage has been confirmed in rice, maize, Arabidopsis , and other plants [ 9 11 ]. Wang reported that high humidity significantly reduced the seed lifespan of ‘Huanghuazhan’ rice [ 12 ]. Dong found that the quantitative trait locus (QTL) gene qSS6-1 was related to storage tolerance of seeds [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…AtPIPLC4 is up-regulated after salt stimulation (Tasma et al, 2008). In addition, overexpression of AtPIPLC5 and AtPIPLC7 improves plant drought tolerance (Zhang et al, 2018c;Van Wijk et al, 2018). At-PIPLC2-silenced plants are more susceptible to bacterial and fungal infections, suggesting that AtPIPLC2 is involved in plant immune response (D'Ambrosio et al, 2017).…”
Section: Introductionmentioning
confidence: 99%